2008
DOI: 10.4067/s0370-41062008000200002
|View full text |Cite
|
Sign up to set email alerts
|

Tratamiento de la anemia con eritropoietina y hierro en Enfermedad Renal Crónica

Abstract: Erythropoietin and iron in anemia management in chronic renal failureAnemia is one of the most common manifestations of Chronic Renal Failure (CRF), specially during the dialysis period. Growth failure and a high cardiovascular morbimortality are 2 of the most important consequences. Objective: To present a review of the current concepts in diagnosis and management of anemia in pediatric CRF patients. Erythropoietin (EPO) deficit is the main cause of anemia, requiring exogenous replacement through intravenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
1
0
3
Order By: Relevance
“…As observed in other studies, patients who received ESAs had lower baseline Hb values, and the observed Hb increase was larger than in those who did not receive ESAs ( 19 ). Patients with kidney disease and iron deficiency are known to require higher doses of ESAs ( 19 ), and the administration of IV iron increases sensitivity to ESAs, making it possible to lower ESA dosages ( 20 , 21 ). In our study, we did not evaluate, the impact on the ESA dose prescribed due its retrospective design and the fact that the study aim was to evaluate tolerance and effectiveness of FCM on the short term.…”
Section: Discussionmentioning
confidence: 99%
“…As observed in other studies, patients who received ESAs had lower baseline Hb values, and the observed Hb increase was larger than in those who did not receive ESAs ( 19 ). Patients with kidney disease and iron deficiency are known to require higher doses of ESAs ( 19 ), and the administration of IV iron increases sensitivity to ESAs, making it possible to lower ESA dosages ( 20 , 21 ). In our study, we did not evaluate, the impact on the ESA dose prescribed due its retrospective design and the fact that the study aim was to evaluate tolerance and effectiveness of FCM on the short term.…”
Section: Discussionmentioning
confidence: 99%
“…La ferritina en plasma representa la reserva de fi erro en los depósitos del organismo (hígado, bazo, médula ósea), recomendándose mantener valores por sobre 100 μg/mL para lograr una adecuada síntesis de hemoglobina 2, 8,38 . En pacientes en hemodiálisis se recomiendan niveles sobre 200 μg/mL.…”
Section: Anemiaunclassified
“…Este mecanismo también actúa a nivel intestinal. El resultado de este desbalance es la carencia de fi erro biodisponible para la eritropoyesis 2, 8,40 .…”
Section: Anemiaunclassified
See 1 more Smart Citation